KEBUTUHAN PESERTA DIDIK DAN RANCANG BANGUN MEDIA PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH - Gazali, Erfan; Saefuloh, Hasan (Arabi : Journal of Arabic Studies, 2019)
This study aimed to map the Arabic learning needs of Islamic senior high school students (Madrasah Aliyah) in the Cirebon city and Cirebon regencies. This research is the first and second stage of the four stages of the 'Four Door' (4D) research model. The 4D research model has four stages: (1) Defining, (2) Design, (3) Developing, and (3) Disseminating. The "Define" stage includes analysis of student needs. Questionnaire was used as an instrument in analyzing these needs. The needs analysis questionnaire was distributed to students to identify their needs and targets for learning Arabic. Respondents consisted of Madrasah Aliyah students in the 2018-2019 academic year totaling 612 students. Data from the needs analysis questionnaire were analyzed using frequency distributions and percentages and the results were then used as a basis for designing and developing e-learning learning models that matched their learning needs and targets. In the 'design' stage, the flipped classroom learning model was used and elaborated with learning theories, namely the constructive learning environment theory (Constructivist Learning Environment-CLEs), Learning Management System (LMS), and Flipped classroom.